2007
DOI: 10.1590/s0101-20612007000200019
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1 and ochratoxin A in beers made in Brazil

Abstract: Samples of beer made in Brazil were analyzed for the presence of fumonisin B 1 (FB 1 ) and ochratoxin A (OTA). FB 1 was searched for in 58 beer samples from 30 plants located in nine states. The samples were concentrated and cleaned up with strong ion exchange column, derivatized with OPA and analyzed by HPLC with fluorescence detection. The limit of detection was 0.26 ng.mL -1 and the average recovery was 98%. Twenty-five samples contained FB 1 ranging from 1 to 40 ng.mL -1 . Beer (123 samples) from 36 plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Considering FB 1 , the results presented previously are similar to a study carried out in Brazil in 2007, where 43.1% of the industrial beers analyzed were contaminated with levels ranging from 1 to 40 mg/l (Kawashima et al 2007). Furthermore, the results from this survey were in agreement with previous European studies: Bertuzzi et al (2011) detected FBs in 97% of the samples (n ¼ 32) at maximum levels of 30 mg/l and Torres, Sanchis, and Ramos (1998) detected FBs in 43.8% of Spanish beer (n ¼ 32) at levels of 4.8e85.5 mg/l.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Considering FB 1 , the results presented previously are similar to a study carried out in Brazil in 2007, where 43.1% of the industrial beers analyzed were contaminated with levels ranging from 1 to 40 mg/l (Kawashima et al 2007). Furthermore, the results from this survey were in agreement with previous European studies: Bertuzzi et al (2011) detected FBs in 97% of the samples (n ¼ 32) at maximum levels of 30 mg/l and Torres, Sanchis, and Ramos (1998) detected FBs in 43.8% of Spanish beer (n ¼ 32) at levels of 4.8e85.5 mg/l.…”
Section: Discussionsupporting
confidence: 84%
“…As beer production requires the use of barley grains and these may have been exposed to mycotoxins, a number of studies have been carried out to detect these in commercially available beers (Benesova, Belakova, Mikulíkov a, & Svoboda, 2012;Kawashima, Vieira, & Valente Soares, 2007;Scott, 1996). In summary, results showed that the deoxynivalenol (DON), nivalenol, T-2, HT-2, diacetoxyscirpenol, zearalenone, aflatoxins, ochratoxin A, and fumonisins have been detected in beers at trace (ppb) levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a following survey on 304 samples of Canadian and imported beer, the toxin was found only in some samples from India (highest value 0.230 mg l À1 ), Spain, Portugal and Mexico (all lower than 0.02 mg l À1 ) (Mably et al, 2005). Regarding FBs, several surveys reported widespread concentrations of fumonisin B 1 (FB 1 ), but generally lower than 100 mg l À1 (Scott & Lawrence, 1995;Kawashima, Vieira & Valente Soares, 2007;Torres, Sanchis & Ramos, 1998;Hlywka & Bullerman, 1999;Dasko, Rauova, Belajova & Kovac, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies not detected OTA in any of the commercial corn kernel samples analyzed (Caldas et al 2002;Magnoli et al 2006b) Few studies regarding OTA occurrence in other substrates are available from Latin America. Kawashima et al (2007) evaluated OTA content on beers produced in different locations in the states of Paraná, São Paulo, Rio de Janeiro, Paraíba, and Pará. Ochratoxin A was found in 4 % of the samples and the concentrations ranged from 1 to 18 ng/mL.…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 99%
“…The presence of OTA has been reported in a wide range of foods and beverages, in body fluids, and in kidneys of animals and humans (EFSA 2006). Natural occurrence of OTA in Latin America has been observed in coffee, wines, beers, grapes, dried grapes, species, cereals, and derivates destined for humans and animals (Iamanaka et al 2005;Taniwaki 2006;Chulze et al 2006;Magnoli et al 2006aMagnoli et al , 2007aKawashima et al 2007;Rosa et al 2009;Shundo et al 2009;Ponsone et al 2010;Vega et al 2012;Vanesa and Ana 2013). The maximum limits for OTA are regulated in many countries but not in Latin America countries.…”
Section: Introductionmentioning
confidence: 99%